Ethical and Organizational Dimensions of AI in Strategic Innovation - Mubarok, Ramdanil; Mubarok, Ahmad; Zulkarnain, Ahnis (Indonesian Scientific Publication, 2024)
Artificial Intelligence (AI) has emerged as a transformative force in strategic innovation management, reshaping decision-making, competitive advantage, and long-term strategies. This narrative review aims to synthesize evidence on AI’s role in fostering innovation while addressing the challenges of its adoption. Literature was systematically retrieved from major academic databases including Scopus, PubMed, and Google Scholar, using targeted keywords such as Artificial Intelligence, Strategic Innovation Management, Predictive Analytics, and Dynamic Capabilities. Inclusion criteria prioritized peer-reviewed studies published between 2014 and 2025 in English, with exclusions applied to non-empirical and non-accredited sources. The findings reveal that AI enhances organizational competitiveness through predictive analytics, optimizes innovation processes in the Fuzzy Front End, and supports long-term strategies when integrated with blockchain and the Internet of Things. Comparative perspectives demonstrate that developed countries leverage robust infrastructure for rapid adoption, while developing nations increasingly use AI-driven mobile solutions to overcome traditional barriers. However, persistent challenges including privacy concerns, data security risks, and algorithmic bias threaten equitable adoption, with organizational dynamic capabilities emerging as crucial determinants of success. Policy implications emphasize the need for regulatory frameworks, investment in digital infrastructure, and workforce reskilling. Future research should address underexplored contexts such as small and medium-sized enterprises and conduct longitudinal studies to assess AI’s enduring impact on organizational resilience. Overall, AI’s transformative potential can only be realized through responsible, context-sensitive, and ethically informed strategies that balance innovation with sustainability.